Vocal Turn-Taking in Families With Children With and Without Hearing Loss. Issue 3 (6th October 2021) - Kondaurova, Maria V.; Zheng, Qi; VanDam, Mark; Kinney, Kaelin
Abstract : Objective: Vocal turn-taking is an important predictor of language development in children with and without hearing loss. Most studies have examined vocal turn-taking in mother-child dyads without considering the multitalker context in a child's life. The present study investigates the quantity of vocal turns between deaf and hard-of-hearing children and multiple members of their social environment. Design: Participants were 52 families with children who used hearing aids (HA, mean age 26.3 mo) or cochlear implants (CI, mean age 63.2 mo) and 27 families with normal-hearing (NH, mean age 26.6 mo) children. The Language ENvironment Analysis system estimated the number of conversational turns per hour (CTC/hr) between all family members (i.e., adult female, adult male, target child, and other child) during full-day recordings over a period of about 1 year. Results: The CTC/hr was lower between the target child and the adult female or adult male in the CI compared with the HA and NH groups. Initially, CTC/hr was higher between the target child and the adult female than between the adult male or the other child. As the child's age increased, turn-taking between the target child and the adult female increased in comparison to that between the target child and the adult male. Over time, turn-taking between the target child and the other child increased and exceeded turn-taking between the target child and the adult caregivers. The increase was observed earlier in families with siblings compared with those without. Conclusions: The quantity of vocal turn-taking depends on the degree of child hearing loss and the relationship between the children and the members of their social environment. Longitudinally, the positive effect of an assistive device on the quantity of turns between the children and their family members was found. The effect was stronger in families with siblings.